Discriminating skilled coaching goups: Quantitative examination of developmental experiences and activities - Young, B. W.; Jemczyk, K.; Brophy, K.; Côté, J. (International Journal of Sports Science and Coaching, 2009)
Literature suggests that the pathway to coaching excellence involves progression through incremental skilled coaching groups over extended durations. Critical in this development is the immersion of developing coaches in various domains of engagement and learning over time. Using a retrospective survey, this study quantified the cumulative activities, experiences, and interactions that competitive-stream Canadian track and field coaches experienced in formal coaching education, active coaching experience, mentoring, and former athletic experience domains. Analyses identified critical experiences that discriminated between four incremental skill groups: local club (n = 24), senior club (n = 19), provincial (n = 10), and national coaches (n = 18). Results demonstrated that certain measures in each of the domains discriminated between the groups, including years of coaching, interactive hours working with athletes, having more assisting coaches whom one has mentored, and having taken more post-secondary coaching courses. These variables, along with former athletic experience prerequisites, were attached to a preliminary between-group developmental framework.